2017
DOI: 10.21873/anticanres.12164
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cure of Intrahepatic Cholangiocarcinoma After Hepatic Resection

Abstract: R0 resections achieved a cure in 45.7% of this series of ICC patients. The predictors of a cure identified here, i.e., absence of lymph node metastasis and absence of microvascular invasion, could contribute to the selection of patients who are not candidates for adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Several studies have reported increasing incidence of ICC in the last decades ( 5 , 6 ) and the 5-year survival rate is still lower than 10% ( 7 ). At present, hepatectomy is still the most effective treatment for long-term survival of ICC patients ( 8 , 9 ), and several poor prognostic factors have been reported, including lymph node metastasis, microvascular invasion (MVI), tumor size ≥5 cm, and multiple nodules ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported increasing incidence of ICC in the last decades ( 5 , 6 ) and the 5-year survival rate is still lower than 10% ( 7 ). At present, hepatectomy is still the most effective treatment for long-term survival of ICC patients ( 8 , 9 ), and several poor prognostic factors have been reported, including lymph node metastasis, microvascular invasion (MVI), tumor size ≥5 cm, and multiple nodules ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the status of MVI is difficult to detect by radiographic images and can only be determined by histological evaluation after hepatectomy ( 14 ). In addition, MVI can affect the selection of personalized therapeutic regime, for instance, ICC patients without MVI do not need to receive adjuvant chemotherapy after R0 resections ( 10 ). Herein, the preoperative determination of MVI status is of great value in ICC patients, and it holds promises for effective patient management and estimation of outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Radical surgical resection is an acceptable form of curative treatment. However, there are no noticeable symptoms in the early stage of cholangiocarcinoma [1]; thus, patients are usually diagnosed in the advanced or metastatic stages of the disease, making it difficult to perform 2 of 17 surgical resection [2][3][4]. In the past decade, the incidence of cholangiocarcinoma has rapidly increased globally [5], necessitating the development of strategies for early diagnosis and effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to its insidious onset and high malignancy, it is often found in advanced stages at diagnosis [10]. Therefore, the surgical resection rate of cholangiocarcinoma is low [11, 12]. It is of increasing clinical importance to evaluate the resectability of the tumor before operation.…”
Section: Introductionmentioning
confidence: 99%